1,500 stretches the complete guide to flexibility and movement - Liebman, Hollis Lance (New York, NY Black Dog & Leventhal Publishers, 2017)
Presents a collection of stretches organized by body part intended to offer pain relief, increased flexibility, and improvements to one's physical appearance.--
Introduction -- The benefits of stretches -- Stretching techniques -- Anatomy -- Section one. Targeted stretches -- Head and neck stretches -- Shoulder stretches -- Arm stretches -- Back stretches -- Chest stretches -- Core stretches -- Upper-leg stretches -- Lower-leg stretches -- Section two. Specialist stretches -- Dance stretches -- Dynamic stretches -- Partner stretches -- Yoga stretches -- Pregnancy stretches.
Includes index.
Keywords: Stretching exercises